The memory improving effects of round scad (Decapterus maruadsi) hydrolysates on sleep deprivation-induced memory deficits in rats via antioxidant and neurotrophic pathways. Issue 12 (6th November 2019) - Zhang, Qi; Su, Guowan; Zhao, Tiantian; Wang, Shuguang; Sun, Baoguo; Zheng, Lin; Zhao, Mouming
Abstract : Sleep deprivation negatively influences memory formation and consolidation, which leads to memory impairment associated with oxidative stress and neurotrophic pathways. Abstract : Sleep deprivation negatively influences memory formation and consolidation, which leads to memory impairment associated with oxidative stress and neurotrophic pathways. In this study, a sleep-deprived rat model was used to evaluate the protective effects of round scad hydrolysates (RSH, 333 and 666 mg per kg bw) on memory impairment and the underlying mechanisms. The result of the Morris water maze test revealed that RSH significantly reversed the cognition deficits induced by sleep deprivation. Moreover, RSH supplementation alleviated oxidative stress by increasing the activities of glutathione peroxidase and superoxide dismutase and the ratio of glutathione/oxidized glutathione in the brain. Furthermore, RSH significantly up-regulated the expression of antioxidant defense-related proteins, including nuclear factor E2-related factor 2 (Nrf2) and its downstream heme oxygenase-1 (HO-1), as well as the phosphorylation of Akt in rats. Moreover, RSH improved the expression of brain-derived neurotrophic factor (BDNF), the phosphorylation of cAMP response element-binding (CREB) and tropomyosin-related kinase B (TrkB) in vivo, indicating that RSH can also promote the expression of proteins related to the neurotrophic pathway. Additionally, UPLC-qTOF-MS/MS was further used to identify the peptides in RSH. The results indicated that RSH mainly consists of low molecular weight peptides with hydrophobic, aromatic and positively charged amino acids in sequence. Taken together, these findings demonstrate that RSH exerts memory-improving actions by regulating the antioxidant and neurotrophic pathways, and RSH can be a potential functional ingredient for the prevention and protection of cognitive deficits.